Effect of estrogen therapy, soy isoflavones, and the combination therapy on the submandibular gland of ovariectomized rats - Chaves Carvalho, Vinicius Diniz [UNESP]; Sarmento Silveira, Vanessa Avila; do Prado, Renata Falchete; Carvalho, Yasmin Rodarte [UNESP] (Elsevier Gmbh, Urban & Fischer Verlag, 2011)
The objective of this study was to evaluate the effect of estrogen deficiency, estrogen therapy, and soy isoflavones on the salivary glands in female rats. Ninety-six animals were ovariectomized, and 24 were sham-operated. Among the ovariectomized rats, 24 received 17 beta-estradiol; 24 received isoflavone extract; 24 received a combination therapy of both; and 24 received water as placebo. The submandibular glands were histomorphometrically analyzed. As a result, the ANOVA test revealed that the hormonal deficiency affected the acini and the ducts of ovariectomized rats, reducing their percentage compared to the sham group. All treatments caused an increase in ducts and acini compared to the placebo group. It was concluded that the estrogen deficiency may be related to salivary gland function due to a reduction in the quantity of salivary acini and ducts secondary to ovariectomy. The estrogen therapy, soy isoflavone therapy, and the combination of both are effective in reducing the effects of ovariectomy on the salivary glands. (c) 2011 Elsevier GmbH. All rights reserved.
Keywords: Salivary glands; Ovariectomy; Estrogen therapy; Isoflavones